Hemosuccus pancreaticus following Parathyroidectomy for Primary parathyroid adenoma - Wu, Wenming; Yang, Yunsheng; Sun, Gang; Cai, Fengchun; Yan, Bin (Turkish Journal of Gastroenterology, 2014)
Abstract Hemosuccus pancreaticus is defined as intermittent bleeding from the pancreatic duct into the GI tract, usually caused by the rupture of an pseudoaneurysm, which is usually associated with pancreatitis, abdominal surgery, and can result in life-threatening hemorrhage. Hyperparathyroidism is a rare cause of pancreatitis, it should be suspected in all patients with a history of primary hyperpara¬t hyroidism , When these diseases coexist, the course of pancreatitis can be rather severe and often complicated. This report detail a case of Hemosuccus pancreaticus due to hyperparathyroidism associated pancreatitis and its successful emergency conservative management by Embolization Techniques.